PEMANFAATAN HASIL ANALISIS NOVEL BROKEN STRINGS KARYA AURELIE MOEREMANS DALAM PEMBELAJARAN BAHASA INDONESIA - Melita, Melvi; Aditya Damayanti, Deasy; Arifin, Zainal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning plays an important role in developing language competence and strengthening students’ character through literary appreciation. This study aims to describe the utilization of the findings from the analysis of Aurelie Moeremans’ novel Broken Strings in Indonesian language learning. The study employed a descriptive qualitative approach using document analysis. The data consisted of secondary data from previous studies on figurative language and psychological meanings in the novel. Data were collected through documentation and literature studies and analyzed using the Miles and Huberman interactive model. The findings show that the analysis of Broken Strings can be used as literary appreciation material to improve students’ ability to identify figurative language, interpret meanings, think critically, empathize, and reflect on human experiences. The novel also contains character values such as respect for human dignity, social awareness, rejection of violence, personal responsibility, and moral awareness. Therefore, the findings provide an alternative learning resource that integrates language competence, literary appreciation, and character development in Indonesian language learning.